2022
DOI: 10.1177/20503121221095485
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of comorbidities and associated risk factors in Indian patients of community-acquired pneumonia

Abstract: Objective: Comorbidities and risk factors have a major implication on incidence, complications, mortality, and management of community-acquired pneumonia complications and treatment outcomes. This study attempts to identify the same in the Indian population through a systematic review and meta-analysis. Methods: We screened observational studies (between January 1990 and February 2021) that reported potential comorbidities and other factors associated with increased risk of community-acquired pneumonia in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…For instance, we previously revealed that comorbidities were independent risk factors influencing in-hospital mortality in patients over 80 years old with CAP 21 . As well, Ghia et al found comorbid conditions like chronic obstructive pulmonary disease, hypertension were common risk factors for CAP in the Indian population 22 . On this basis, we propose that more attention should be paid to the care of comorbidities in elderly patients with CAP, especially aged over 85.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, we previously revealed that comorbidities were independent risk factors influencing in-hospital mortality in patients over 80 years old with CAP 21 . As well, Ghia et al found comorbid conditions like chronic obstructive pulmonary disease, hypertension were common risk factors for CAP in the Indian population 22 . On this basis, we propose that more attention should be paid to the care of comorbidities in elderly patients with CAP, especially aged over 85.…”
Section: Discussionmentioning
confidence: 89%
“…Community-acquired pneumonia (CAP), defined as pneumonia acquired outside the hospital, is one of the most common infectious diseases in clinical practice [ 1 , 2 ]. The incidence of pneumonia increases with age, with a 10 times higher hospitalization rate in patients aged 65 years and older (about 2000 per 100,000 per year) than in the younger population [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Developing countries bear a significant brunt of the disease, impacting healthcare. 1 Many literatures show that CAP has a high incidence and hospitalization rate (11‰ and 4‰, respectively) and is more likely to recurrence. 2 , 3 , 4 , 5 With the medical interventions level gets more and more advanced and the treatment methods are constantly developing, however, the mortality rate of this disease has not decreased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Community‐acquired pneumonia (CAP) is a global disease. Developing countries bear a significant brunt of the disease, impacting healthcare 1 . Many literatures show that CAP has a high incidence and hospitalization rate (11‰ and 4‰, respectively) and is more likely to recurrence 2–5 .…”
Section: Introductionmentioning
confidence: 99%